Social Support Pada Pegawai di Kabupaten Nagan Raya - Fitriani, Rita; Damrus, Damrus; Mardaleta, Mardaleta (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study aims to validate the construct of social support for employees in Nagan Raya Regency based on six dimensions of the Social Provisions Scale (SPS), attachment, social integration, reassurance of worth, reliable alliance, guidance, and opportunity for nurturance to help. The approach used is a quantitative descriptive with a cross-sectional design. The determination of the number of samples refers to the number of indicators, which is 5 to 10 times the number of indicators, resulting in 120 respondents selected using a cluster sampling technique. Data analysis was carried out using the Covariance-Based Structural Equation Modeling (CB-SEM) method using AMOS. The results of the analysis show that all dimensions have a standardized regression weight value 0.5, a construct reliability (CR) value 1.96, and a p-value 0.05. The estimated values are: attachment (estimate = 0.796; p = 0.000), social integration (estimate = 0.986; CR = 3.776; p = 0.000), reassurance of worth (estimate = 0.348; CR = 2.919; p = 0.004), reliable alliance (estimate = 0.765; CR = 4.073; p = 0.000), guidance (estimate = 0.584; CR = 3.960; p = 0.000), and opportunity for nurturance (estimate = 0.368; CR = 2.687; p = 0.007). All hypotheses are accepted. This finding confirms that the six dimensions are valid components in the construct of social support in the work environment of Nagan Raya Regency employees.